THE DYNAMICS OF TRADITION AND MODERNIZATION: A COMPARATIVE STUDY OF ISLAMIC RELIGIOUS EDUCATION AT AL-AZHAR UNIVERSITY AND UIN SUNAN KALIJAGA - Faizah, Ima; Faridi, Faridi; Tobroni, Tobroni (Antis-Publisher, 2024)
Objective: This study aims to compare the modernization of Islamic education systems at Sunan Kalijaga State Islamic University (UINSUKA), Indonesia, and Al-Azhar University, Cairo, Egypt. Method: A qualitative descriptive approach was employed using library research to analyze policies and practices of both institutions in adapting to modernization. Results: The findings reveal significant differences in the modernization characteristics of the two universities. Al-Azhar University prioritizes preserving Islamic traditions while incorporating secular sciences, maintaining global relevance. Conversely, UINSUKA emphasizes innovation through an integrative-interconnected paradigm, focusing on local adaptability. Despite their differing approaches, both institutions aim to ensure the relevance of Islamic education in their respective contexts. Novelty: This study provides a comparative analysis of two prominent Islamic universities' approaches to modernization, highlighting distinct strategies shaped by global and local influences.